Family law in America - Katz, Sanford N., 1933- (New York : Oxford University Press, 2014)
This title examines family law in America and the tension between individual autonomy and governmental regulation. The book analyzes the definitions of formal marriage and informal marriage, the extent to which relationships established before marriage are regulated, and how marriage is being redefined to take into account equality of the sexes. Also examined are divorce procedures, alimony, assignment of property upon divorce, determining what is marital property and what is separate property, child custody, and how additional models are being developed to take into account new family forms.
Includes bibliographical references and index.
Description based on online resource; title from home page (viewed on September 24, 2014).
Keywords: Domestic relations -- United States